Iodine-catalyzed synthesis of fused tetracyclic pyridazino[6, 1-b]pyrrolo[1, 2-a]quinazolin-9(1H)-one derivatives via a tandem reaction. Issue 17 (28th April 2016) - Zhang, Wen-Ting; Qiang, Wen-Wen; Yao, Chang-Sheng; Wang, Xiang-Shan
Abstract: A facile and general method for the synthesis of pyridazino[6, 1- b ]pyrrolo[1, 2- a ]quinazolin-9(1 H )-one derivatives via a reaction of 2-aminobenzohydrazide and 1, 7-dichloro-heptan-4-one catalyzed by iodine in the presence of excess NaHCO3 is described. This is a tandem reaction to construct three new rings and a chiral quaternary carbon center in one-pot procedure. Two possible pathways in the formation of the second heterocycle are proposed, and they are confirmed by the key intermediates of pyrrolo[1, 2- a ]quinazolin-5(1 H )-ones which are selectively obtained via controlling the ratio of base. Graphical abstract: A facile and general method for the synthesis of pyridazino[6, 1- b ]pyrrolo[1, 2- a ]quinazolin-9(1 H )-one derivatives via a reaction of 2-aminobenzohydrazide and 1, 7-dichloro-heptan-4-one catalyzed by iodine in the presence of excess NaHCO3 is described. Two possible pathways in the formation of the second heterocycle are proposed, and they are confirmed by the key intermediates of pyrrolo[1, 2- a ]quinazolin-5(1 H )-ones which are selectively obtained via controlling the ratio of base.